Jatropha Oil Cake Based Activated Carbon for Symmetric Supercapacitor Application: A Comparative Study on Conventional and Hydrothermal Carbonization Processes. Issue 4 (27th January 2020) - Siva Sankari, M.; Vivekanandhan, S.
Abstract: Jatropha oilcake (JOC), a major agro industrial co‐product was effectively converted into activated carbons employing KOH mediated chemical process for supercapacitor applications. The activated carbons were synthesized by employing conventional (CC) as well as hydrothermal carbonization (HTC) processes and investigated their impact on their physicochemical properties. The graphitization degree of the pristine and activated biocarbons was investigated through XRD and RAMAN analysis. BET surface area analysis showed the enhanced specific surface area of the pristine carbons from 71.5 (CC) and 48.1 (HTC) m 2 /g into 678.1 (CC) and 746.7 m 2 /g (HTC) through KOH activation. The synthesized activated biocarbon materials were explored as the electrode material for supercapacitors. The electrochemical analysis of the fabricated symmetric supercapacitor showed the specific capacitance of 145.76 F/g and 174.78 F/g at 1 A/g for the activated biocarbons obtained respectively through conventional and hydrothermal carbonization processes. Also, they showed considerable energy density of 5.28 Whkg −1 (CC) and 6.49 Whkg −1 (HTC) at a power density of 248.6 and 265.09 W kg −1 . Among the two different approaches, the hydrothermal process showed great promise for the production of renewable biomass‐derived activated biocarbon materials for supercapacitor applications. Abstract : The Jatropha oilcake was effectively converted into pristine and activated biocarbons employing conventional and hydrothermal carbonizations. Activation process enhanced the specific surface area of Jatropha oilcake based carbon materials, which showed higher specific surface area. The synthesized pristine and activated biocarbons were explored for supercapacitor applications. Activated biocarbon derived through hydrothermal carbonization showed highest specific capacity of 174.78 F/g.